(untitled) (Global Journal of Computer Science and Technology, 2013)
The aim of this study has been to identify Human- Computer Interaction HCI design methods and techniques for the development of cross-platform e-commerce websites that can be used on multiple devices with different screen sizes and web browsers The findings presented here are based on a theoretical framework consisting of three categorizations composition continuity and consistency The framework was implemented with the aid of a case study and a prototype implementation that adapts to the user context The development of the prototype was based on the evaluation of existing e-commerce websites Identified usability issues were readability and the fact that tasks should be dependent on the user context The overall results of this study are presented as a set of usability guidelines for cross-platform e-commerce which highlight the importance of identifying the users needs as well as the context in which they operate by offering a common set of functionality between devices and using device specific input mechanisms